Thermoanalytical study of the complexes of 4-dimethylaminocynnamylidenepyruvate with manganese (II), cobalt (II), nickel (II), copper (II), zinc (II) and lead (II), in the solid state - Schnitzler, Egon; Lazzarotto, Márcio; Carvalho-Filho, Marco Aurelio da Silva; Ionashiro, Massao (Eclética Química, 2002)
Solid state compounds M-4-DMCP, where 4-DMCP is 4-dimethylaminocinnamylidenepyruvate and M represents Mn (II), Co (II), Ni (II), Cu (II), Zn (II) and Pb (II) were prepared. These compounds were studied by thermoanalitycal techniques: thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometric titration with EDTA. From the results obtained by the complexometric titration with EDTA, TG, DTG and DSC curves, was possible to establish the hydration degree, stoichiometry and thermal stability of the prepared compounds.